Identification of risk factors for open conversion from laparoscopic cholecystectomy for acute cholecystitis based on computed tomography findings - Hirohata, Ryosuke; Abe, Tomoyuki; Amano, Hironobu; Hanada, Keiji; Kobayashi, Tsuyoshi; Ohdan, Hideki; Noriyuki, Toshio; Nakahara, Masahiro (Surgery Today, 2020)
Purpose Laparoscopic cholecystectomy (LC) is performed widely for acute cholecystitis (AC). This study was conducted to identify the predictors for conversion cholecystectomy (CC) for AC. Methods The subjects of this study were 395 patients who underwent emergency surgery for AC between 2011 and 2019. Univariate and multivariate analyses were performed to establish the significance of the risk factors for CC in patients with grades II and III AC. Results There were 162 TG18 GII and GIII patients in the LC group and 31 in the CC group. Univariate analysis revealed significant differences in performance status ( p = 0.039), C-reactive protein levels ( p = 0.016), albumin levels ( p = 0.002), gallbladder (GB) wall thickness ( p = 0.045), poor contrast of the GB wall ( p = 0.035), severe inflammation around the GB ( p < 0.001), enhancement of the liver bed ( p = 0.048), and duodenal edema ( p < 0.001) between the groups. Multivariate analysis identified hypoalbuminemia ( p = 0.043) and duodenal edema ( p = 0.014) as independent risk factors for CC. Conclusions Most patients with grade I AC underwent LC and had better surgical outcomes than those with grades II and III AC. The most appropriate surgical procedure should be selected based on preoperative imaging of the GB and the neighboring organs and by the presence of hypoalbuminemia.